Biological activity of some plants extract against in the survival of rate adult Oryzaephilus surinamensis (Coleopteran Silvanaidae) - Yonus, May ’I.; Abdul-Kareem, Shaimaa; Mahdii, Beadaa Abdalqader (Iraqi Journal of Science, 2022)
A laboratory study was conducted to evaluate the effect of crud extracts from seven plant species (Nigella sativa, Eugenia caryophylota, Corianderum sativum, Piper nigrum, Peganum hermala, Achillea santolina, Citrullus colocynthis) belong to different families tested as food feeding toxicity against adult of Oryzaephilus surinamensis. The results of the current study showed that hexane extracts from all plants used were more influential in all used concentrations than, the alcoholic extract, and hexane extract of Hanzal was more effective reaching survival rate of adult to 58.3% at concentration of 10% then the plant yarrow and black pepper about 66.2%, and 67.3% respectively, at the same concentration. While the survival rate was approximate in black bean, cloves, and rue at the same concentration 76.4%, 71.3%, and 77.3%. Respectively. The alcoholic extract of Hanzal was less effects on the survival of the adults it 70.0%, while the coriander plant least in fluently of all plants used in the study, as were 80%. In additional to the toxic action and anti-fed ant effect, preliminary results indicated that many of plant extracts have potential in giving good protections of stored plant from attacking by insect, they are indigenous and many be safe and readily available to protection granaries from attacking by insect pestes.